Dos teorías de la modernidad y una crítica - Rivero, Ángel (Foro Interno, 2007)
Modernity has been seen as the final stage of the most radical process of change in the history of humanity. According to the modernist theorists, modern society was to be equated with the total abolition of all the evils of traditional society and the establishment of a totally free, egalitarian and rich society. This was the prophetic message of Marx, but the actual development of modernisation ended with modernity on trial. The actual experience of socialism was a modernist nightmare, which suggests that the whole modernity project should be re-assessed. This article offers a comparison of the theories of modernity proposed by Marx and the Hungarian sociologist, Ágnes Heller, concluding with a possible future for modernity after the demise of its messianic dreams.